Mobilization of the blaKPC-14 gene among heterogenous plasmids in extensively drug-resistant hypervirulent Klebsiella pneumoniae - Wang, Lin; Shen, Weiyi; Cai, Jiachang (Frontiers in Microbiology, 2023)
Introduction Ceftazidime/avibactam (CZA) is an effective alternative for the treatment of infections caused by KPC-producing carbapenem-resistant Klebsiella pneumoniae (CRKP). However, KPC variants with CZA resistance have been observed in clinical isolates, further limiting the treatment options of clinical use. Methods In this study, we isolated three KPC-14-producing CRKP from two patients in intensive care units without CZA therapy. The antimicrobial susceptibility was determined using the broth microdilution method. Three CRKP were subjected to whole-genome sequencing to analyze the phylogenetic relatedness and the carriage of antimicrobial resistance genes and virulence factors. Long-read sequencing was also performed to obtain the complete sequences of the plasmids. The horizontal transfer of the blaKPC-14 gene was evaluated by conjugation experiments. Results Three CRKP displayed resistance or reduced susceptibility to ceftazidime/avibactam, colistin, and tigecycline. Single-nucleotide polymorphism (SNP) analysis demonstrated the close phylogenetic distance between these strains. A highly similar IncFII/IncR plasmid encoding blaKPC-14 was shared by three CRKP, with blaKPC-14 located in an NTEKPC-Ib element with the core region of ISKpn27- blaKPC-14-ISKpn6. This structure containing blaKPC-14 was also observed in another tet(A)-carrying plasmid that belonged to an unknown Inc-type in two out of three isolates. The horizontal transferability of these integrated plasmids to Escherichia coli EC600 was confirmed by the cotransmission of tet(A) and blaKPC-14 genes, but the single transfer of blaKPC-14 on the IncFII/IncR plasmid failed. Three CRKP expressed yersiniabactin and carried a hypervirulence plasmid encoding rmpA2 and aerobactin-related genes, and were thus classified as carbapenem-resistant hypervirulent K. pneumoniae (hvKP). Discussion In this study, we reported the evolution of a mosaic plasmid encoding the blaKPC-14 gene via mobile elements in extensively drug-resistant hvKP. The blaKPC-14 gene is prone to integrate into other conjugative plasmids via the NTEKPC-Ib element, further facilitating the spread of ceftazidime/avibactam resistance.